Large Magnetic Polyoxometalates Containing the Cobalt Cubane ‘[CoIIICo3II(OH)3(H2O)6–m(PW9O34)]3−' (m = 3 or 5) as a Subunit - Duan, Yan; Clemente-Juan, Juan M.; Giménez-Saiz, Carlos; Coronado, Eugenio (Frontiers in Chemistry, 2018)
A synthetic procedure is presented to construct new magnetic polyoxometalates (POMs) containing one or two subunits of '[CoIIICoII3(OH)3(H2O)6 m(PW9O34)]3−' (m = 3 or 5). The substitution of the water ligands present in these subunits by oxo or hydroxo ligands belonging to other POM fragments, gives rise to four, larger POM anions: [Co7(OH)6(H2O)6(PW9O34)2]9– (2), [Co7(OH)6(H2O)4(PW9O34)2]n9n− (2'), [Co11(OH)5(H2O)5(W6O24)(PW9O34)3]22– (3) and [{Co4(OH)3(H2O)(PW9O34)}2{K⊂(H2W12O41)2}{Co(H2O)4}2]17− (4). The crystal structures, magnetic characterization and stabilities in aqueous solutions of these POM derivatives are also presented.